Patriarchal Stereotypes that marginalise African Women: A Feminist Analysis of Sindiwe Magona’s Beauty’s Gift (2008) - Refiloe, Nkadimeng; Montle, Malesela Edward (Technium Social Sciences Journal, 2021)
This study sought to examine patriarchal stereotypes which are held against African women through Sindiwe Magona’s Beauty’s Gift (2008). Patriarchal assumptions have always trivialised women and placed them in subordinate positions. Thus, this study aimed to ascertain how patriarchal traditions with the aid of colonial systems have oppressed women and still to do so and minimise their authentic voices and access to opportunities. This qualitative paper has endeavoured to unmask the patriarchal stereotypes that repress and hinder the success of women through the textual analysis of Magona’s sampled novel. A feminist literary theory has been employed as a lens that reflects on how women subvert the oppressive systems to attain self-realisation and the reason why other women remain oppressed by these systems. The study inter alia has found that the emergence of female African writers such as Magona has challenged and corrected the stereotyped female representation in African societies and also highlighted the importance of women coming together to find tactics of attaining empowerment.